The NAMES of DOOMS DAY and its DRAMATIZED in TABARAK PART - Ebrahi, Idan; Hassan, Ahmad (Islamic Sciences Journal, 2023)
The believe of the Dooms day is the fifth pillar from the six believes for Islam ‎and one of its fundamentals of Islamic religion and great origin of believes ‎origins there for it is no believes truth without the great pillar. We want to ‎remember in this time because the humans is forget it and they preferring the ‎live and forget the Dooms day. The Holy Quraan in Tabarak part to remember ‎that and what is happened and difficulties in that day to know Human that will ‎see it. There for we focused at the dooms day our research that its tittle (The ‎Names of Dooms Day and its Dramatized in Tabarak part – Creedal Study-).‎ The scientific materials forced at us that research has an introduction, ‎preface and two researches add the end. We mention in preface definitions of ‎tittle and its vocabulary.‎ The first research- the names of dooms day that mentions in Tabarak part ‎and the second research- the dramatized of Dooms day that refer it in Tabarak ‎part. ‎